Gonzalez V. Roman Catholic Archbishop of Manila and its contributions to American Civil Church Law - Johnson, Joseph B. (Perspective in the Arts and Humanities ASIA (formerly Asian Perspectives in the Arts and Humanities), 2016)
The tension between the religion clauses of the First Amendment to the United States Constitution, guaranteeing the non-establishment of religion and prohibiting the restriction of its free exercise,is clearest when secular courts are called upon to adjudicate the internal disputes of religious organizations. Such a dispute was at heart of the 1929 case of Gonzalez V. Roman Catholic Archibishop of Manila, in which the plaintiff alledged his right to be appointed to an ecclesiastical benefits in accordance with the terms of the canon law in force at the time of its erection rather than the more stringent provisions of the 1917 Code of Canon Law then in force. A minor in the development of principles of the resolution of church disputes by secular courts. Gonzalez's greater significance lies in its status as a forerunner of the ministerial exception, the legal doctrine which immunizes "religious entities from discrimination suits brought by employees with 'ministerial' responsibilities such as teaching doctrine or leading worship.